NFAT is a nerve activity sensor in skeletal muscle and controls activity-dependent myosin switching - McCullagh, Karl J. A. (National Academy of Sciences, 2004)
Calcineurin (Cn) signaling has been implicated in nerve activity-dependent fiber type specification in skeletal muscle, but the downstream effector pathway has not been established. We have investigated the role of the transcription factor nuclear factor of activated T cells (NFAT), a major target of Cn, by using an in vivo transfection approach in regenerating and adult rat muscles. NFAT transcriptional activity was monitored with two different NFAT-dependent reporters and was found to be higher in slow compared to fast muscles. NFAT activity is decreased by denervation in slow muscles and is increased by electrostimulation of denervated muscles with a tonic low-frequency impulse pattern, mimicking the firing pattern of slow motor neurons, but not with a phasic high-frequency pattern typical of fast motor neurons. To determine the role of NFAT, we transfected regenerating and adult rat muscles with a plasmid coding for VIVIT, a specific peptide inhibitor of Cn-mediated NFAT activation. VIVIT was found to block the expression of slow myosin heavy chain (MyHC-slow) induced by slow motor neuron activity in regenerating slow soleus muscle and to inhibit the expression of MyHC-slow transcripts and the activity of a MyHC-slow promoter in adult soleus. The role of NFAT was confirmed by the finding that a constitutively active NFATc1 mutant stimulates the MyHC-slow, inhibits the fast MyHC-2B promoter in adult fast muscles, and induces MyHC-slow expression in regenerating muscles. These results support the notion that Cn-NFAT signaling acts as a nerve activity sensor in skeletal muscle in vivo and controls nerve activity-dependent myosin switching.